2019
DOI: 10.2147/ndt.s195379
|View full text |Cite
|
Sign up to set email alerts
|

<p>Plasma levels of IL-6 in patients with untreated major depressive disorder: comparison with catecholamine metabolites</p>

Abstract: ObjectiveIL-6 and catecholamines play roles in the pathophysiology of major depressive disorder (MDD).AimThe present study investigated associations between plasma IL-6 and plasma catecholamine metabolites in patients with MDD.Participants and methodsA total of 148 patients (male/female 65/83, age 49.5±12.1 years) who met the criteria for MDD based on the Diagnostic and Statistical Manual of Mental Disorders IV and 40 participants as healthy controls (HC; male/female 23/17, age 44.0±10.5 years) were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Although we previously reported that plasma IL-6 levels 48 and serum BDNF levels 9 were associated with scores on the Hamilton Rating Scale for Depression among patients with major depression, we observed no correlations among serum IL-6 levels, BDNF levels, and MADRS scores in the present study. It is possible that most patients enrolled in the present study had mild-to-moderate depression.…”
Section: Discussioncontrasting
confidence: 99%
“…Although we previously reported that plasma IL-6 levels 48 and serum BDNF levels 9 were associated with scores on the Hamilton Rating Scale for Depression among patients with major depression, we observed no correlations among serum IL-6 levels, BDNF levels, and MADRS scores in the present study. It is possible that most patients enrolled in the present study had mild-to-moderate depression.…”
Section: Discussioncontrasting
confidence: 99%
“…In children with inflammatory medical conditions, the risk of depression in adulthood may be high because of permanent effects as a result of early exposure to stress, high levels of CRP, and raised leucocyte count and IL-6 [ 67 ]. An increased level of IL-6 in CSF is associated with a decrease in serotonin metabolites, which contributes to depression, but no relationship between IL-6 and catecholamines has been found [ 68 ]. A raised IL-6 level for ≥ 6 months plays an important role in the occurrence of depression [ 66 ], and more suicide attempts are seen in people with an increased CSF IL-6 level [ 67 ].…”
Section: Mechanisms Of Depression In Ra: Effects Of Inflammatory Cytomentioning
confidence: 99%
“…IL-6 has a significant relationship with major depressive disorder (MDD) [ 66 ], and IL-6 inhibitors are considered effective in selective serotonin reuptake inhibitor (SSRI) refractory major depression cases [ 67 , 66 , 68 ]. Sarilumab, by targeting IL-6, improves depression in RA patients [ 60 ].…”
Section: Mechanisms Of Depression In Ra: Effects Of Inflammatory Cytomentioning
confidence: 99%
“…For instance, studies of serum IL-6, ICAM-1, and VCAM-1 levels in AD patients and depression patients show some differences. Serum IL-6 levels were higher in AD patients than depression patients [24][25][26]. VCAM-1 serum levels also appeared to be greater in AD patients compared to depression patients [27,28].…”
Section: Diagnosismentioning
confidence: 80%